Regional Variations in Italian Coffee Culture: Historical Influences and Contemporary Preferences for Robusta-Arabica Blends - Mariano Peluso (Proceedings)
Coffea canephora, or Robusta, plays an important role in the Italian coffee scene, particularly in the preparation of espresso, contributing to the coffee’s intense flavor and rich crema. But why do Italians prefer this type of coffee? Why does this preference not emerge in the same way in neighboring countries such as Germany, France, Austria, and even Spain? And why are there so many differences in coffee tastes among regions within Italy? The northern part of the country prefers lighter and longer coffees with a major presence of Arabica, while southern regions prefer shorter and darker coffees with a larger presence of Robusta. This kaleidoscopic coffee culture traces back to historical events linked to the introduction of coffee beans in Italy and to its varied regional landscape. Within the folds of history lie the origins that have shaped the Italian coffee identity. This journey presents an intriguing case study.